Aptamers: current challenges and future prospects - Rozenblum, Tomas Guido (2015)
Introduction: Aptamers are oligonucleotide molecules raised in vitro from large combinatorial libraries of nucleic acids and developed to bind to targets with high affinity and specificity. Whereas novel target molecules are proposed for therapeutic intervention and diagnostic, aptamer technology has a great potential to become a source of lead compounds.Areas Covered: In this review the authors address the current status of the technology and highlight the recent progress in aptamer-based technologies. They also discuss the current major technical limitations of aptamer technology and propose original solutions based on existing technologies that could result in a solid aptamer-discovery platform.Expert opinion: Whereas aptamers have shown to bind to targets with similar affinities and specificities to those of antibodies, aptamers have several advantages that could outweigh antibody technology and open new opportunities for better medical and diagnostic solutions. However, the current status of the aptamer technology suffers from several technical limitations that slowdown the progression of novel aptamers into the clinic and makes the business around aptamers challenging.